A SUGGESTED SOLUTION TO LINE VERSUS STAFF PROBLEMS IN ORGANIZATION THEORY - Kindig, Frederick E. (Academy of Management Journal, 1961)
Suggests a solution to the conflict between the role of line executives and staff executives in organization theory. Areas of conflict; Description of several examples; Details of the approach to the conflict problem.